Empowering women through the positive birth movement. Issue 3 (3rd April 2019) - Hallam, Jenny; Howard, Chris; Locke, Abigail; Thomas, Melissa
Abstract: Childbirth has been positioned as a life changing event that has profound long-term psychological effects upon women. This paper adopts a community psychology approach to explore the role that the Positive Birth Movement (PBM) may have in tackling negative birth experiences by supporting women before and after birth. Six women who all regularly attend UK-based PBM meetings and had given birth to at least one child participated in one to one semi-structured interviews designed to explore the support they received before, during and after their birth, as well as their experiences with the PBM. A Foucauldian inspired discourse analysis explores themes relating to the lack of support and information provided by the NHS and the function of the PBM as a transformative community space which offers social support and information. Within these themes a focus on neoliberalism, choice and the woman's position as an active consumer of health care is critically discussed. It is argued that the PBM has the potential to prepare women for positive birth experiences but more attention needs to be paid to the wider contexts that limit women's ability to make 'free' choice.